Case Report: Lung adenocarcinoma associated with germline ERCC2 frameshift mutation - Liu, Lili; Cui, Jia; Liu, Siye; Pan, Evenki; Sun, Limin (Frontiers in Oncology, 2023)
Family history is an established risk factor for lung cancer. Previous studies have found that germline mutations of EGFR, BRCA1, BRCA2, CHEK2, CDKN2A, HER2, MET, NBN, PARK2, RET, TERT, TP53 and YAP1 were associated with lung cancer risk. The study reports the first of a lung adenocarcinoma proband with germline ERCC2 frameshift mutation c.1849dup (p. A617Gfs*32). Her family cancer history review demonstrated that her two healthy sisters, a brother with lung cancer and two healthy cousins were positive for ERCC2 frameshift mutation, which might contribute to increased cancer risk. Our study highlights the necessity of performing comprehensive genomic profiling in discovering rare gene mutations, early cancer screening and following monitoring for patients with family cancer history.